Cover Image, Volume 2, Number 2, June 2020. Issue 2 (15th June 2020) - Su, Zhong; Ling, Han Yeu; Li, Meng; Qian, Shangshu; Chen, Hao; Lai, Chao; Zhang, Shanqing
Abstract : Cover image : Li‐I2 battery could deliver higher energy and power density than some existing Li‐ion batteries. In order to realize such a tremendous potential, a carbon energy research team by Shanqing Zhang at Griffith University developed a simple "salty" thermal treatment to convert a coffee extract into a functional honeycomb‐like carbon materials as an interlayer (article number 10.1002/cey2.40 ) to overcome the inherent barriers of Li‐I2 battery, i.e., inhibit the dissolution and the shuttle of iodine. Consequently, the as‐prepared Li‐I2 battery achieved high energy and power density performance with excellent cycle stability.